Pengaruh Manajemen Modal Kerja Terhadap Profitabilitas (Studi pada Perusahaan Retail yang Terdaftar di BEI Periode 2012-2013) - Ingtiyas, Rasmi Anindita; SE, Sumiati (Jurnal Ilmiah Mahasiswa FEB, 2014)
The purpose of this research is to determine the impact of working capital management on profitability of retail companies listed on Indonesia Stock Exchange (IDX)for the period 2012 to 2013. The efficiency of working capital can be measured by using cashconversion cycle (CCC). Cash conversion cycle has 3 components: days of sales in inventory(DSI), days of sales outstanding (DSO), and days of payables outstanding (DPO). These 3components of cash conversion cycle are used as independent variable of this research. Meanwhile, net profit margin (NPM) is used to asses firm’s profitability. So, NPM is the dependent variable of this research. This is an explanatory research by using quantitativeapproach. Multiple linear regression analysis is used to determine the impact of working capital management on profitability. The result of this research shows that DSI, DSO, and DPO simultaneously have significant impact on NPM. In the other hand, DSI and DPO have positive significant impacton NPM partially. DSO has no significant impact on firm’s NPM partially. Furthermore,based on this research, DPO has dominant impact in determining firm’s profitability which is assesed by NPM.Keywords:Working Capital, Days of Sales in Inventory (DSI), Days of Sales Outstanding (DSO), Days of Payables Outstanding (DPO), Profitability, Net Profit Margin (NPM), Retail Companies